Towards an Integrated Approach to Recording Military Aircraft Crash Sites - Masters, Peter; Osgood, Richard (​Forensic Archaeology, Anthropology and Ecology, 2021)
The forensic investigation of military aircraft crash sites has become in recent times part of mainstream traditional archaeology. Mostly amateur aircraft enthusiasts have undertaken the recovery of military aircraft crash sites without methodically recording the remains. The sites covered in this paper have been approached based on recording the in-situ remains methodically using traditional and scientific methods used in the field of archaeology from fieldwalking, metal detecting and geophysics. The strategy and methodology used in this investigation showed how effective and important it is to recover as much of the remains as possible to place it into a meaningful context in order to understand the reasoning for why these aircraft came to a devasting end by crashing into the ground at great speed. The excavations have involved Operation Nightingale—an MOD based recovery programme that specializes in archaeology. This paper will demonstrate the importance of using such an integrated approach to the recovery of military aircraft crash sites from the Second World War by referring to specific case studies.